Witness Protection Regime in the Indian Criminal Justice System: Addressing Gaps and Proposing Reforms - Dr. Anand Kumar Vishwakarma; Ankita shukla (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The criminal justice system serves as the cornerstone of any society governed by the rule of law. In India, the system’s efficacy is measured by its ability to ensure justice, maintain law and order, and protect the fundamental rights of its citizens. Witnesses, often referred to as the “sentinels of justice,” play an indispensable role in this framework. Their testimonies can make or break a case, acting as the bridge between crime and conviction. The criminal justice system in India, while undergoing significant reforms, faces challenges in ensuring the safety and protection of witnesses. However, witnesses often face significant risks, including threats, harassment, and physical harm, which undermine their ability to testify freely and truthfully. The need for a robust witness protection mechanism is thus essential to safeguard their interests and uphold the integrity of the justice system. Due to intimidation, threats, and even violence, faced by witnesses, leading to a reluctance to come forward and testify. This not only undermines the prosecution’s case but also perpetuates a culture of impunity for criminals. To address this issue, the Indian government has implemented various measures, including the Witness Protection Scheme, 2018, which provides protection to witnesses in specific categories of crimes. However, the effectiveness of this scheme has been questioned due to limited resources, lack of awareness, and inadequate implementation.